In silico and in vitro Evaluation of Mimetic Peptides as Potential Antigen Candidates for Prophylaxis of Leishmaniosis - Guedes, Deborah Carbonera; Santiani, Manuel Hospinal; Carvalho, Joyce; Soccol, Carlos Ricardo; Minozzo, João Carlos; Machado de Ávila, Ricardo Andrez; de Moura, Juliana Ferreira; Ramos, Eliezer Lucas Pires; Castro, Guillermo Raul; Chávez-Olórtegi, Carlos; Thomaz-Soccol, Vanete (Frontiers in Chemistry, 2021)
Antigen formulation is the main feature for the success of leishmaniosis diagnosis and vaccine, since the disease is caused by different parasite species that display particularities that determine their pathogenicity and virulence. It is desirable that the antigens are recognized by different antibodies and are immunogenic for almost all Leishmania species. To overcome this problem, we selected six potentially immunogenic peptides derived from Leishmania histones and parasite membrane molecules obtained by phage display or spot synthesis and entrapped in liposome structures. We used these peptides to immunize New Zealand rabbits and determine the immunogenic capacity of the chimeric antigen. The peptides induced the production of antibodies as humoral immune response against L. braziliensis or L. infantum. Next, to evaluate the innate response to induce cellular activation, macrophages from the peptide mix-immunized rabbits were infected in vitro with L. braziliensis or L. infantum. The peptide mix generated the IFN-γ, IL-12, IL-4 and TGF-β that lead to Th1 and Th2 cellular immune response. Interestingly, this mix of peptides also induced a high expression of iNOS. These results suggest that the mix of peptides derived from histone and parasites membrane molecules was able to mimic parasites proteins and induce cytokines important to CD4+ T cell Th1 and Th2 differentiation and effector molecule to control the parasite infection. Finally, this peptide induced an immune balance that is important to prevent immunopathological disorders, inflammatory reactions and control the parasite infection.